Multi-dimensional perovskites with improved thermal stability - Chaudhary, Bhumika (Nanyang Technological University, 2022)
Methylammonium lead iodide (MAPbI3) has revolutionized the photovoltaic field thanks to its excellent optoelectronic properties. Perovskite solar cells (PSCs) based on MAPbI3, even reaching high power conversion efficiencies (PCE), suffers from ambient instability under external factors such as heat. Indeed, the volatile organic MA+ cation in MAPbI3 together with its polycrystalline film nature and defects/trap density, also determine its heat tolerance. These defects/trap sites also promote ionic movement, charge-carrier recombination within the bulk, and PSC interfaces resulting in the drop of PCE and long-term stability of PSCs. In context to develop more robust perovskite materials, the dimensional engineering of perovskite has emerged as a promising strategy. The multi-dimensional perovskites comprise two-dimensional (2D) and three-dimensional (3D) perovskite network combination offering balance in charge transport and ambient stability. In this thesis, the impact of multi-dimensionality in altering the heat tolerance of MAPbI3 perovskite is explored. The strategies consist of embedding bulky organic ligand with 3D MAPbI3 to form multi-dimensional perovskites and study the heat tolerance of perovskites at elevated temperatures. In the first study, a series of mixed dimensional naphthylmethylammonium lead iodide (NMA)2(MA)n-1PbnI3n+1 perovskite is prepared by incorporating naphthylmethylammonium iodide (NMAI) bulky organic ligand with methylammonium iodide (MAI) forming a mixed (2D+3D) configuration and evaluating their heat tolerance. Investigations on optical, structural, morphological, and vibrational properties revealed that structural integrity of mixed dimensional perovskite is retained during thermal ageing, in contrast to 3D MAPbI3 perovskite, due to passivation of grain boundaries and reduced defects in mixed dimensional polycrystalline film and inhibition of the MA+ diffusion. In the second study, the multi-dimensional perovskite was obtained by embedding NMAI ligand atop of 3D MAPbI3 perovskite to form bilayer (2D/3D) heterostructure perovskites, and comparative analysis of heat tolerance of best performing mixed (2D+3D) and bilayer (2D/3D) perovskites are presented. Investigation revealed that mixed dimensional matrix (2D+3D) perovskite possesses better heat tolerance during ex-situ and in-situ thermal ageing than that of best-performing bilayer 2D/3D perovskite, owing to distribution of 2D perovskite throughout the bulk, compact grains network, and effective suppressed non-radiative recombination. Moreover, the heat tolerance of co-evaporated 3D MAPbI3 (C-MAPbI3) perovskite and the possible role of multi-dimensional (2D/3D) perovskites in altering its heat tolerance is highlighted. The result analysis showed that the C-MAPbI3 perovskite possesses better thermal stability than solution-processed 3D MAPbI3, and its heat tolerance is significantly improved further by embedding the NMAI ligand atop of it forming 2D/3D bilayer perovskites. Finally, the solution processed 3D, and multi-dimensional perovskites (2D+3D and 2D/3D) are implemented in PSCs architecture, and their photovoltaic characteristics and heat tolerance of PSCs are evaluated. Overall, this thesis emphasizes the correlation between dimensional engineering of MAPbI3 perovskite and its role in altering the heat-induced structural disintegration. The comparative investigation of heat tolerance of mixed (2D+3D) and bilayer (2D/3D) multi-dimensional perovskites highlighted the need to choose a suitable configuration to maximize the thermal stability and understand the thermal degradation aspects of multi-dimensional perovskites. Moreover, the dimensional engineering (2D/3D) of co-evaporated MAPbI3 offers a way to improve its thermal stability aspect further.